Mapping the Human Rights Issues from the Perspective of Students in a Private Religious-based University: A Case Study - Kaumpungan, Bayu; Paculanang, Lerie Grace Caagbay (12th International Scholars Conference 2025, 2026)
Human rights education had been a prominent matter in human rights. However, when it comes to religious institution, the topic remains underexplored. This study explores the topics of human rights among college level participants who are currently studying in a religious-based higher institution. The aim of the study is to measure the depth of knowledge of students in the religious based higher educational institution. Twelve participants joined the study in a form of focus group discussion exchanging ideas on human rights through ten semi-structured questions. The result indicates that while most participants possess a substantial level of knowledge, the religious belief of the institution conflicts with certain individual rights that they believe in. This result may be used as a baseline to help religious-based educational body especially in higher education to relook on how human rights education being taught in their respective institution.